2016
DOI: 10.3389/fpsyg.2016.01865
|View full text |Cite
|
Sign up to set email alerts
|

The Association of DRD2 with Insight Problem Solving

Abstract: Although the insight phenomenon has attracted great attention from psychologists, it is still largely unknown whether its variation in well-functioning human adults has a genetic basis. Several lines of evidence suggest that genes involved in dopamine (DA) transmission might be potential candidates. The present study explored for the first time the association of dopamine D2 receptor gene (DRD2) with insight problem solving. Fifteen single-nucleotide polymorphisms (SNPs) covering DRD2 were genotyped in 425 unr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
(63 reference statements)
0
16
0
1
Order By: Relevance
“…Details about the participants have been described in a previous study (Zhang & Zhang, 2016). Briefly, the participants were 425 unrelated healthy Han Chinese college students (76.7% females, M age = 18.9 years, SD = 0.84) without self-reported history of psychiatric disorder.…”
Section: Methodsmentioning
confidence: 99%
“…Details about the participants have been described in a previous study (Zhang & Zhang, 2016). Briefly, the participants were 425 unrelated healthy Han Chinese college students (76.7% females, M age = 18.9 years, SD = 0.84) without self-reported history of psychiatric disorder.…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral venous blood sample was collected from each participant and genomic DNA was extracted using the method described in a previous study (Zhang & Zhang 2016). The SNP selection was largely based on Jiang et al's study (rs737865,rs5993883,rs4633,rs6267,rs4818,rs4680).…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…To the best of our knowledge, there are only two recent genetic studies on insight problem solving that are related to convergent thinking. In both studies, classical insight problems were presented, and the performance scores were found to be correlated with polymorphisms of two SNPs in DRD2 (rs1800467 & rs6278) ( Zhang & Zhang, 2016 ) and one SNP in COMT (rs5993883) ( Jiang, Shang & Su, 2015 ). As insight problem solving is suggested to reflect a kind of convergent thinking ( Jiang, Shang & Su, 2015 ), these results provide preliminary evidence for the possible genetic involvement for convergent thinking.…”
Section: Introductionmentioning
confidence: 99%